Analysis of Elementary Teacher Readiness in Developing Probolinggo Elementary School IKM-Based Learning Modules - Regina, Belinda Dewi; Suwandayani, Beti Istanti; Kuncahyono, Kuncahyono; Rizqi, Evi (Journal Of Teaching And Learning In Elementary Education, 2024)
Research related to analyzing teacher readiness in implementing the Independent Curriculum is very important to carry out. The objectives of this research are: Analyzing indicators of teacher readiness in the Readiness to Implement the Independent Curriculum. Apart from that, this research will also provide recommendations for increasing teacher readiness in compiling teaching modules based on the Independent Curriculum. This research method uses descriptive qualitative, data collection is carried out through FGD (Focus Group Discussion). The instruments used were observation guidelines, interviews and a questionnaire on Readiness to Implement the Independent Curriculum. Data were analyzed using data triangulation techniques. Based on the research results, it was concluded that the readiness of elementary school teachers in implementing IKM in Probolinggo Regency was included in the medium category. The aspect of readiness in understanding the assessment is one of the assessments that is relatively low.